STRATEGI PENGELOLAAN SAMPAH BERKELANJUTAN DI PADUKUHAN JOMBLANG: MENUJU LINGKUNGAN BERSIH DAN SEHAT - Hidayatullah; Wilis Fahlefi; Purnama Andri Murdapa; Prihartanto Eko Wibowo; Eka Yulianta; Saimin (LPPM Akademi Manajemen Administrasi Yogyakarta, 2025)
Household waste management is one of the major challenges in Indonesia, particularly in rural areas that often lack integrated waste processing facilities. This community service program was implemented in Padukuhan Jomblang, Sendangadi Village, Mlati, Sleman, with the aim of addressing waste issues through community-based approaches and the application of sustainable practices. A participatory method was employed to empower the local community, including training on composting and creative recycling as practical and environmentally friendly solutions. Additionally, the program sought to integrate environmental sustainability with economic opportunities by utilizing organic and inorganic waste.The results revealed a significant reduction in household waste volume, increased community awareness of sustainable waste management, and the development of economic potential, such as the creation of creative products from recycled materials. This program demonstrated that community-based waste management not only contributes to a cleaner and healthier environment but also provides long-term social and economic benefits. These findings offer a replicable model for other areas with similar conditions.